Co-Cities: Innovative Transitions toward Just and Self-Sustaining Communities - Sheila R. Foster; Christian Iaione (The MIT Press, 2022)
A new model of urban governance, mapping the route to a more equitable management of a city's infrastructure and services. The majority of the world's inhabitants live in cities, but even with the vast wealth and resources these cities generate, their most vulnerable populations live without adequate or affordable housing, safe water, healthy food, and other essentials. And yet, cities also often harbor the solutions to the inequalities they create, as this book makes clear. With examples drawn from cities worldwide, Co-Cities outlines practices, laws, and policies that are presently fostering innovation in the provision of urban services, spurring collaborative economies as a driver of local sustainable development, and promoting inclusive and equitable regeneration of blighted urban areas. Identifying core elements of these diverse efforts, Sheila R. Foster and Christian Iaione develop a framework for understanding how certain initiatives position local communities as key actors in the production, delivery, and management of urban assets or local resources. Within this framework, they explain the forms such initiatives increasingly take, like community land trusts, new kinds of co-housing, neighborhood cooperatives, community-shared broadband and energy networks, and new local offices focused on citizen science and civic imagination. The "Co-City" framework is uniquely rooted in the authors' own decades-long research and first-hand experience working in cities around the world. Foster and Iaione offer their observations as "design principles"—adaptable to local context—to help guide further experimentation in building just and self-sustaining urban communities.
Keywords: 320; the commons; commons; equity; cities; smart cities; creative cities; city as commons; urban commons; urban governance; co-governance; co-creation; urban law; urban policy; urban innovation; sustainable development; equitable development; community development